(untitled) (Chittagong University Journal of Biological Sciences, 2024)
In our daily life, drinking water is one of the most essential elements. However, safe and good-quality drinking water is a major concern for human health. Therefore, our study assessed the sanitation, hygiene conditions, and evaluation of bacterial population of drinking water in 40 schools in the port city, of Bangladesh. Total viable count (TVC), total coliform count (TCC), and survey questionnaire were used to complete our study. About 65% of water samples exceeded the acceptable limit (>500 cfu/ml) detected by TVC. The most probable number (MPN) method was used to see the presence of coliform bacteria where about 65% of samples were found contaminated with coliform, among them 12.5% of samples were at very high risk according to World Health Organization (WHO) guidelines. A total of 10 bacterial isolates like Enterobacter sp., E. coli, Klebsiella sp., Salmonella sp., Proteus sp., Serratia sp., Citrobacter sp., Pseudomonas sp., Alcaligenes sp., and Micrococcus sp. were detected in water samples by using four selective media and then identified by using cultural, morphological and biochemical tests. The disc diffusion method was used to detect antibiotic sensitivity with 10 commercially available antibiotics. About 80% of isolates were found completely resistant to erythromycin, amoxicillin, ampicillin, and rifampin and 90% were sensitive to ciprofloxacin, gentamicin, azithromycin, and tetracycline. Antibiotic resistance isolates might pose a serious threat to human health. In most schools, reservoirs of drinking water were found contaminated by various bacteria. Only 48.3% of schools used separate toilets for girls but of poor-quality hygiene and sanitation facilities. Due to poor hygiene, sanitation, and contaminated drinking water, students may suffer from various diseases. Therefore, this study emphasizes the need to raise awareness about hygiene and sanitation facilities by regularly monitoring school drinking water quality to ensure children are out of waterborne diseases. Chittagong Univ. J. B. Sci. Vol. 12 (1 & 2): 130-142, 2024